Implementasi Sistem Pemantauan Fermentasi Eco Enzyme Berbasis Internet of Things sebagai Model Standardisasi Mutu Berbasis Data pada Komunitas Pengelola Sampah - Sely Novita Sari; Bagus Gilang Pratama; Rizal Maulana; Nanda Ramadhani; Sophia Anwar Fayyal Jannah (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2026)
Rumah Sampah Ringas Trengginas is a community-based organic waste management group in Baturetno, Banguntapan, Bantul, that produces eco enzyme from kitchen waste. Before this programme, fermentation was conducted manually without measurement instruments, systematic records, or standard operating procedures, so product quality varied between batches and fermentation failure was difficult to detect early. Unlike previous community service programmes that focused on production training, this programme developed a data-driven fermentation quality standardisation model for waste management communities. The programme involved four core partner members and surrounding residents, and was carried out in five stages are socialisation and needs assessment, device design and assembly, development of the recording and notification system, on-site installation and partner training, and evaluation. The device used an ESP32 microcontroller integrated with pH, TDS, NPK, and DS18B20 temperature sensors, TLS/SSL-encrypted MQTT data transmission, an early-warning buzzer, and web- and mobile-based interfaces. Success was evaluated through three instruments sensor accuracy testing against calibrated portable meters (ten paired measurements per parameter per batch), measurement of daily monitoring time before and after the intervention, and a partner competency checklist. The main outputs were an installed IoT monitoring device, a web- and mobile-based recording system, a copyright-registered production SOP, and an industrial design application. Preliminary testing of three batches showed a mean accuracy of 95% with pH of 3.5–3.7 and temperature of 28.5–29.0 °C under normal fermentation conditions; daily monitoring time fell from 60 to 18 minutes (70% efficiency); and all core members operated the system independently. The findings indicate that the system can support community-scale fermentation standardisation, although validation on a larger number of batches is still required.  Keywords: Eco enzyme; Internet of Things; Fermentation Monitoring; Organic Waste; Quality Standardization.